1984
DOI: 10.1002/jez.1402290318
|View full text |Cite
|
Sign up to set email alerts
|

Effects of house fly oostatic hormone on egg development neurosecretory hormone action in Aedes atropalpus

Abstract: Oostatic hormone, prepared from mature female house flies, Musca domestica, was examined for its effect on processes mediated by egg development neurosecretory hormone (EDNH). When injected into newly emerged adult female mosquitoes, Aedes atropalpus, oostatic extracts inhibited vitellogenic growth of the ovaries. Comparison of oostatic activities in heads, thoraces, and abdomens of house flies showed that the major portion was present in the abdomens, apparently associated with the ovaries. In contrast to unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Genetic analysis indicates that autogeny is monofactoral and not sex linked (O'Meara and Craig, 1969;Gwadz, 1970;O'Meara and Krasnick, 1970;O'Meara, 1972;Masler et al, 1981). Prior studies also clearly establish that maturation of a first clutch depends on the release of neurohormones from the brain, which stimulates ECD production by the ovaries, mobilization of teneral nutrient reserves in the fat body, and VG production (Van Handel, 1976;Fuchs et al, 1980;Masler et al, 1980;Masler et al, 1981;Masler et al, 1983;Birnbaum et al, 1984;Kelly et al, 1981;Kelly et al, 1984;Ma et al, 1984). The central question of this study was whether OEH and ILPs, which regulate egg maturation in A. aegypti, also regulate egg production in G. atropalpus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis indicates that autogeny is monofactoral and not sex linked (O'Meara and Craig, 1969;Gwadz, 1970;O'Meara and Krasnick, 1970;O'Meara, 1972;Masler et al, 1981). Prior studies also clearly establish that maturation of a first clutch depends on the release of neurohormones from the brain, which stimulates ECD production by the ovaries, mobilization of teneral nutrient reserves in the fat body, and VG production (Van Handel, 1976;Fuchs et al, 1980;Masler et al, 1980;Masler et al, 1981;Masler et al, 1983;Birnbaum et al, 1984;Kelly et al, 1981;Kelly et al, 1984;Ma et al, 1984). The central question of this study was whether OEH and ILPs, which regulate egg maturation in A. aegypti, also regulate egg production in G. atropalpus.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicate that ECD production by the ovaries and yolk uptake by oocytes rise and fall within 10-50h post-eclosion (PE) followed by oviposition at 60-72h PE Masler et al, 1980;Masler et al, 1981;Birnbaum et al, 1984;Kelly et al, 1981;Kelly et al, 1984). Decapitation of G. atropalpus females immediately after eclosion blocks yolk uptake into oocytes, while injection of crude head extracts from A. aegypti and 20-hydroxyecdysone (20E) partially rescue egg maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory activity toward ecdysteroidogenesis was also detected in larval extracts of C. vicina (8,9). Injection of crude extracts from the housefly, Musca domestica, into the mosquito, Aedes atropalpus, reduced ecdysteroid synthesis and inhibited egg development (10,11). Grb-AST, a group of allatostatins isolated from the adult brain of the cricket, Gryllus bimaculatus, decreased the ecdysteroid titer in vivo (12).…”
mentioning
confidence: 98%
“…The discovery of TMOF Antigonadotrophins, or factors that inhibit egg development (oostatic hormones and TMOF), have been demonstrated in the cockroach Blattella germanica (Iwanov and Mescherskaya, 1935), decapod crustaceans (Carlisle and Knowles, 1959) and the housefly Musca domestica (Adams et al, 1968;Kelly et al, 1984). In mosquitoes, Meola and Lea (1972) and Else and Judson (1972) similarly demonstrated an ovary-produced humoral factor secreted during oogenesis that inhibited yolk deposition in less-developed follicles.…”
mentioning
confidence: 99%
“…In M. domestica, oostatic hormone seems to inhibit the release or synthesis of egg developmental neurosecretory hormone (EDNH; Adams, 1981), but in mosquito it was proposed that the hormone acts directly on the ovary (Meola and Lea, 1972). Kelly et al (1984) injected a crude extract of oostatic hormone from M. domestica into the autogenous mosquito Aedes atropalpus and demonstrated inhibition of both egg development and ecdysteroid biosynthesis. Borovsky (1985) reported that the mosquito ovary is a rich source of 'oostatic hormone'.…”
mentioning
confidence: 99%